Relative effects of uniconazole-p and other growth regulators on micropropagation ratio of yam (dioscorea spp.) plantlets at different growth phases (2014)
Scarcity of planting materials, pest and diseases are major constraints to yam production. The tissue culture techniques, meristem culture combined with heat therapy has been used to produce high-yielding virus-tested plantlets of root crops, which are later multiplied through micropropagation. This procedure, however has low regedaration and multiplication rates in yam. We investigated effects of different plant growth regulators on rate of growth of yam plantlets when applied at different growth phases. Three concentrations each of uniconazole-p (UP), gibberellic acid (GA3), jasmonic acid(JA) and naphthalene acetic (NAA) acids were applied at single node and primary nodal complex (PNC) formation phases in a split-plot design using two genotypes each of white and water yam. Number of nodes per plantlet was recorded after 16 weeks. Results showed that number of new nodes varied significantly with genotype by growth phase interaction and the main effect of PGRs. After 16 weeks, the control, 1.7 μM UP and 0.03 μM JA showed highest means of 7, 9 and 8 nodes per plantlet respectively compared to 2-3 nodes in the GA treatments. We demonstrated that 4900, 8100 and 6400 plantlets could be obtained in one year using 100 nodes by sub-culturing them four times. Addition of PGRs at PNC doubled the number of nodes per plantlet. However the effect of stage of treatment varied with genotypes. The GA and its inhibitor, UP influenced the multiplication rate of yam.